A structural model of the PriB–DnaT complex in Escherichia coli replication restart. Issue 3 (13th December 2020) - Abe, Yoshito; Ikeda, Yohei; Fujiyama, Saki; Kini, R. Manjunatha; Ueda, Tadashi
Abstract : In Escherichia coli, DNA replication is restarted following DNA repair by the PriA‐dependent pathway, in which the binding and dissociation of proteins such as PriA, PriB, and DnaT on ssDNA lead to the formation of a protein–DNA complex for recruiting the DnaB–DnaC replication protein complex. However, the structure of the PriB–DnaT complex, which is an essential step in the PriA‐dependent pathway, remains elusive. In this study, the importance of His26 in PriB for replication restart was reconfirmed using plasmid complementation. Furthermore, we used NMR to examine the DnaT interaction sites on PriB. We also evaluated the PriB–DnaT peptide complex model, which was prepared by in silico docking, using molecular dynamic simulation. From these data, we propose a structural model that provides insight into the PriB–DnaT interaction. Abstract :